PERENCANAAN KEUANGAN SYARIAH BAGI KELUARGA PADA DESA CIBITUNG KULON, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Thantawi, Tubagus Rifqy; Rizal, Muhammad; Damayanti (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2023)
This community service aims to increase knowledge and emphasize the importance of Islamic finance for families. The subject of this community service is the people of Cibitung Kulon Village. Pamijahan district. Bogor Regency, West Java Province In community service, activities are carried out based on survey, counseling and training methods as well as activity evaluation. The result of this community service is that people can better understand and know the importance of Islamic financial planning. With this community service, it can be concluded that the visible problems are not only caused by a lack of understanding, but also by people who have not prioritized financial planning within their family environment so that with this community service all participants can understand the importance of sharia financial planning for families.